The Value of Virtual Reality Technology in Embryology Education; Objective and Subjective Outcomes - ALFALAH, SALASABEEL F. M. (International Journal of Psychosocial Rehabilitation, 2020)
Medical education is witnessing a rapid evolution of learning tools, fuelled by the emergence of novel information technologies. Virtual reality (VR) technology and three-dimensional (3D) visualization is gaining popularity in this field. Embryology, a branch of the anatomical sciences, is an area where there is room for the utilization of such technology. The representation of the human embryo within a VR environment could complement current teaching aids and overcome existing shortfalls. The impact of this on the educational outcome, however, has not been extensively evaluated. This paper describes a comparative study evaluating the benefit of VR technology in embryology teaching, by comparing it to an existing tool, namely two-dimensional (2D) images of the human embryo, and a subjective evaluation of students’ views regarding the use of VR to learn the embryology course material. The results showed that VR enhances embryology education when assessed both in a subjective and objective manner.